PEMETAAN PENURUNAN ELASTIS FONDASI TIANG BERDASARKAN DATA SONDIR KOTA PEKANBARU - Muhammad Muhshi muhshin; Agus Ika Putra (Universitas Sebelas Maret, 2020)
Pekanbaru City has developed quite rapidly. Therefore, local governments are aware of thehigh demand for multi-story building construction, so that buildings built with more than two floorsare required to conduct a land subsidence test. The load of a structure will be transmitted by thefoundation to the ground, where the soil is expected to be able to support the load. The soil subsidencetest is obtained from the sondir test data or also called the Dutch Cone Penetration Test (DCPT)which is used to determine the profile into the soil continuously with the value of cone tip resistanceand blanket resistance (Wafi et al., 2013).The purpose of this study is to analyze the calculation ofthe settlement of a single pile foundation based on the foundation bearing capacity data from thesondir data obtained from the Riau University Laboratory using the elastic settlement method. Theresearch stages carried out are reviewing theories related to piles, then collecting data includingdata on the carrying capacity of the foundation and sondir data. The final stage is conductingcalculation analysis. The results of this study obtained a map of the elastic settlement of the pilefoundation at a depth of 6 meters, 12 meters and 18 meters